Survey on attitude toward judo - With Japanese university judo athletes and regular students as subjects - Okazaki, Y.; Okada, R.; Tokuyasu, H.; Moriwaki, Y. (Proceedings of the 2016 International Association of Computer Science in Sport (IACSS) Conference, 2016)
This study examined both Japanese university Judo athletes` and regular students` perceptions of Judo. An opinion survey was administered to both Judo athletes (n=733) and those students inexperienced in Judo. Using a 5-point scale, each subject answered 20 questions derived from Nakajima et al.`s previous study on people`s perceptions of Judo. With the exceptions of questions 12 and 14, the results indicated there were significant differences found in the remaining 18 items based on the years of experience factor. In the results for Q14, Judo was consistently understood to be a traditional Japanese martial art. For Q12, in which respondents were asked about ear injuries, both subjects groups (experienced and inexperienced in Judo) associated this activity with this type of injury.